Histological aspects of Therapeutic effects of Stable gastric pentadecapeptide BPC 157 on stomach perforation - Petra Horvat; Marjeta Linarić Lipnjak; Matej Lacković (Liječnički vjesnik, 2023)
We focused on histological aspects of the cytoprotective effects of Stable gastric pentadecapeptide BPC 157 after stomach perforation in rats was performed.